Breastfeeding Practices during Pregnancy from the Perspective of Women in Makassar City - Bestfy Anitasari; Imami Nur Rachmawaty; Henny Permatasari (State Islamic University of Sunan Ampel, 2019)
The practice of breastfeeding during pregnancy is mostly done by women, including in Indonesia. Previous research has reported inconsistencies. Some people claim that this practice is beneficial and others report the risk among mothers, fetus, and breastfed children. The aim of this study is to interpret the practice of breastfeeding during pregnancy from a woman perspective. This study used interpretative phenomenology design with in-depth interviews with seven participants selected purposively. Data were analyzed using the Van Manen analysis stage and 11 themes were obtained. In general, mothers who breastfeed during pregnancy experienced a dilemma between fulfilling the child's right to breast milk and the desire to stop breastfeeding.